Sistem Pakar Mendiagnosa Penyakit Bawang Merah Dengan Metode Depthfirst Search Backward Chaining - Johanes Perdamenta Sembiring; Jonson Manurung (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
There were 12 disease data obtained from the agriculture and horticulture department of Deli Serdang, namely earthworms, thrips pests, leaf caterpillars, armyworms, aphids, root namhodes, purple spots, powdery mildew, stem neck rot, anthracnose, fusarium wilt, rot. poor, dead shoots (phytopthora porri foister) and there are 30 Symptoms of disease in onion plants An expert system is a computer program that provides expert advice (decisions, recommendations or problem solving) as if people had been consulted. The backward chaining method is the opposite of forward chaining which starts with a hypothesis (an object) and asks for information to convince or ignore. Backward chaining inference engines are often called Object-Driven/Goal-Driven. In this study, a web-based expert system was designed using the backward chaining method which aims to detect the type of disease in shallot plants by paying attention to the symptoms experienced in shallot plants. By using the backward chaining method, the value of disease certainty in shallot plants will be obtained from the expert system designed. The test results concluded that the design of an expert system for diagnosing diseases in shallots using the backward chaining method was as expected.